CLINICAL STUDIES OF L-105 ON RESPIRATORY TRACT INFECTION - AKAISHI, TADAYUKI; ISHIDA, SAKAE; FUJIKANE, TOSHIAKI; MINAMI, HIROAKI; ONODERA, SOKICHI; NAKANO, HITOSHI; TAKASHIO, TETSUYA; SASAKI, NOBUHIRO (CHEMOTHERAPY, 1986)
Clinical studies of L-105, a new cephalosporin were carried out in the field of respiratory tract infection and the following results were obtained. I. L-105 was administered to 8 cases with bacterial pneumonia, one case with lung abscess and one case with chronic bronchitis at a dosage of 2-4 g/day by intravenous drip infusion for 8-14 days. 2. Clinical response of L-105 was excellent in 3 cases, good in 3 cases, fair in 2 cases, poor in one case and undetermined in one case. The efficacy rate was 67%. 3. Skin eruption was observed in one case with autosensitization dermatitis, and slight elevation of GOT, GPT, BUN and eosinophil were observed in two, one and two cases, respectively.